APLIKASI MODEL STIMULUS – ORGANISM – RESPONSE DALAM KEPUTUSAN PEMBELIAN ONLINE - Listyandari, Made Dwi; Wardana, I Made; Kerti Yasa, Ni Nyoman (Buletin Studi Ekonomi, 2016)
Stimulus – Organism – Response Model Aplication in Online Purchasing Decision. The purpose of this study is to analyze the quality of the website and brand websites on online purchase decisions mediated by trust and perceptions of risk. Respondents in this study were 110 customers of online shopping. The method of analysis used the Structural Equation Model. Based on the literature that used the research model using the model of Stimulus Organism Response. The results of this study are of quality websites and brand website has a positive and significant effect to the trust , has a negative and significant effect to risk perception. Trust has a negative and significant effect to risk perception and has a positive and significant effect to purchase decision. Risk perception has a negative and significant effect to purchase decision. In this research is recommended to can create a website that is easy to use by customers and increase customer trust on purchase decisions on online shopping.   Keywords: online shopping, stimulus organism response (SOR), structural equation model  (SEM), customer
Keywords: online shopping, stimulus organism response (SOR), structural equation model (SEM), customer